Faktor faktor yang mempengaruhi turnover intention karyawan di Kota Batam - Mardika, Nanda Harry; Prima, Argo Putra (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to examine the factors that influence employee turnover intention in Batam City. The problem factor is job stress and job satisfaction. The purpose of this study was to determine the effect of job stress and job satisfaction on employee turnover intention partially and simultaneously. The total sample of 96 respondents was taken using a purposive sampling method and then the data were analyzed by using the SPSS program. The methodology in this research is descriptive with a quantitative approach. The results showed that work stress partially had a positive and significant effect on employee turnover intention with a t value of 3.532 and a significant value of 0.001. Job satisfaction partially has a negative and significant effect on employee turnover intention with a t value of -2.509 and a significant value of 0.014. Simultaneously this study shows that job stress and job satisfaction have a positive and significant effect on employee turnover intentions with an at-count value of 13.213 and a significant value of 0.000. The coefficient of determination of the two independent variables together on the dependent variable is 22.1% and 77.9% is influenced by other variables not examined in this study.